2003
DOI: 10.1007/s00709-003-0004-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunological evidence for the presence of plant homologues of the actin- related protein Arp3 in tobacco and maize: subcellular localization to actin-enriched pit fields and emerging root hairs

Abstract: The actin-nucleating and -organizing Arp2/3 protein complex is well known to be conserved throughout the eukaryotic kingdom. For higher plants, however, only limited evidence is available for the presence of the Arp2/3 complex so far. Using heterologous antibodies against the Dictyostelium discoideum and Schizosaccharomyces pombe proteins and a bovine peptide, we found immunological evidence for the presence of Arp3 homologues in plants. First, proteins with a molecular mass of about 47-50 kDa were clearly rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 52 publications
1
24
0
1
Order By: Relevance
“…However, either direct or indirect associations of ARP2/3 with membranes are expected given the wide variety of organelle-based functions for the complex in eukaryotic cells (Eitzen et al, 2002;Fucini et al, 2002;Fehrenbacher et al, 2005;Kaksonen et al, 2005), and the often-observed punctate ARP2/3 localization in mammalian cells reflects a cellular pool of membrane-associated ARP2/3 (Welch et al, 1997;Strasser et al, 2004;Shao et al, 2006). Microsomal ARP2/3 has been reported in plants using a variety of heterologous antibodies (Van Gestel et al, 2003;Fiserova et al, 2006), but the data are conflicting and the extent of membrane association depended on which ARP2/3 subunit antibody was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, either direct or indirect associations of ARP2/3 with membranes are expected given the wide variety of organelle-based functions for the complex in eukaryotic cells (Eitzen et al, 2002;Fucini et al, 2002;Fehrenbacher et al, 2005;Kaksonen et al, 2005), and the often-observed punctate ARP2/3 localization in mammalian cells reflects a cellular pool of membrane-associated ARP2/3 (Welch et al, 1997;Strasser et al, 2004;Shao et al, 2006). Microsomal ARP2/3 has been reported in plants using a variety of heterologous antibodies (Van Gestel et al, 2003;Fiserova et al, 2006), but the data are conflicting and the extent of membrane association depended on which ARP2/3 subunit antibody was used.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of ARP2/3 localization based on the behavior of individual subunits (Le et al, 2003). In some cases, the results are weakened by the unknown specificity of heterologous ARP2/3 antibodies (Van Gestel et al, 2003;Fiserova et al, 2006). A specific antibody was raised against Silvetia ARP2 (Hable and Kropf, 2005).…”
mentioning
confidence: 99%
“…(27,29) In an interesting parallel to the localization of the complex in motile cells, a recent study immunolocalizes the large ARP3 subunit of the complex to the tips of extending root hairs. (64) Why should a major subunit of the complex, ostensibly signifying the presence of the entire complex, be localized at the very tip of an extending non-motile plant cell? Independent observations on tip-extension and actin dynamics in tipgrowing pollen-tubes have also suggested a major role for actin-polymerization in tube extension.…”
Section: Putative Regulatory Molecules For the Complex In Plantsmentioning
confidence: 99%
“…Several other works noted additional internal substructures (Ding et al 1992b, Overall and Blackman 1996. Recently, PD-associated proteins have been identified in charophycean algae and land plants , Blackman and Overall 1998, Gestel et al 2003, Faulkner et al 2005, Sagi et al 2005, Thomas et al 2008, Simpson et al 2009, Faulkner and Maule 2010. These works suggested that there are highly complicated control mechanisms underlying the cell-to-cell molecular traffic via PD.…”
Section: Introductionmentioning
confidence: 98%